Inclusive Histories for inclusive futures: Interactions and entanglements then and now (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
This article makes a case for the production and dissemination of inclusive histories in public dialogue and public spaces of history consumption, includingclassrooms, lecture halls, monuments and textbooks. Inclusive histories are plural and multi-perspectival, meaning that interactions, overlapping phenomena and entanglements between various collectives at both the state and sub-state levels are emphasised. The discussion contends for a national historical narrative that encourages social accord rather than social fracturing without projecting a mythical reconciliatory motif onto the past. It also cautions against the pursuit of sanitised versions of the past and reflects on how discourses of victimhood and indigeneity put at risk the prospects for inclusive futures in pluralistic societies. The article argues that publically consumed commemorations and interpretations of the South African past should reflect the multiplicity of histories and peoples that inhabit the nationa space. It also suggests that re-telling South Africa’s collective past in innovative rather than destructive ways, and in a manner that embraces the inclusive ethos of its constitutional democracy, will assist in producing a more inclusive historical narrative. The arguments in this article are intended to challenge and motivate those engaged in narrating history – amateur historians, history teachers, history  learners, heritage practitioners, and textbook publishers – to represent the past in ways that promote plurality and multi-perspectivity in the present and for the future
Keywords: South Africa; Inclusive histories; History education; Identity; Belonging; Multi-perspectivity; Critical citizenship; Entanglement